Discovery of a novel Kv7 channel opener as a treatment for epilepsy. Issue 21 (1st November 2015) - Davoren, Jennifer E.; Claffey, Michelle M.; Snow, Sheri L.; Reese, Matthew R.; Arora, Gaurav; Butler, Christopher R.; Boscoe, Brian P.; Chenard, Lois; DeNinno, Shari L.; Drozda, Susan E.; Duplantier, Allen J.; Moine, Ludivine; et al.
Graphical abstract: Abstract: Facilitating activation, or delaying inactivation, of the native Kv7 channel reduces neuronal excitability, which may be beneficial in controlling spontaneous electrical activity during epileptic seizures. In an effort to identify a compound with such properties, the structure–activity relationship (SAR) and in vitro ADME for a series of heterocyclic Kv7.2–7.5 channel openers was explored. PF-05020182 (2 ) demonstrated suitable properties for further testing in vivo where it dose-dependently decreased the number of animals exhibiting full tonic extension convulsions in response to corneal stimulation in the maximal electroshock (MES) assay. In addition, PF-05020182 (2 ) significantly inhibited convulsions in the MES assay at doses tested, consistent with in vitro activity measure. The physiochemical properties, in vitro and in vivo activities of PF-05020182 (2 ) support further development as an adjunctive treatment of refractory epilepsy.